Hypocaccus (s.l.) hirsutus sp. nov., an atypical new species of the genus Hypocaccus C. Thomson, 1867 from India (Coleoptera: Histeridae: Saprininae) - Lackner, Tomáš (Zootaxa, 2015)
An atypical new species of Hypocaccus C. Thomson, H. hirsutus sp. nov. from south India is described and figured, but left unassigned to a subgenus. Current problems of taxonomy, morphological characters and inter-relationships of Hypocaccus subgenera are discussed and notes on the distribution of Hypocaccus C. Thomson, 1867 in India are given.